Bio-Fabricated Aluminum Oxide Nanoparticles Derived from Waste Pharmaceutical Packages: Insight into Characterization and Applications - Jamilah M. Al-Ahmari; Reem M. Alghanmi; Ragaa A. Hamouda (Biomolecules, 2025)
This study examines the environmental challenges posed by azo-dye pollutants and aluminum industrial waste. Aluminum oxide nanoparticles (P/Al2O3-NPs) were produced using a green method that utilized pharmaceutical packaging waste as an aluminum source and marine algae extract (Padina pavonica) as reducing and stabilizing agents and that was characterized by XRD, EDX, SEM, TEM, and zeta potential. Batch biosorption studies were performed to assess the effectiveness of P/Al2O3-NPs in removing CR dye from aqueous solutions. The results demonstrate that the particle sizes range from 58.63 to 86.70 nm and morphologies vary from spherical to elliptical. FTIR analysis revealed Al–O lattice vibrations at 988 and 570 cm−1. The nanoparticles displayed a negative surface charge (−13 mV) and a pHzpc of 4.8. Adsorption experiments optimized parameters for CR dye removal, achieving 97.81% efficiency under native pH (6.95), with a dye concentration of 30 mg/L, an adsorbent dosage of 0.1 g/L, and a contact time of 30 min. Thermodynamic studies confirmed that the process is exothermic and spontaneous. Kinetic data fit well with the pseudo-second-order model, while equilibrium data aligned with the Langmuir isotherm. The adsorption mechanism involved van der Waals forces, hydrogen bonding, and π–π interactions, as supported by the influence of pH, isotherm data, and FTIR spectra. Overall, the study demonstrates the potential of eco-friendly P/Al2O3-NPs to efficiently remove CR dye from aqueous solutions.